2008
DOI: 10.5194/acp-8-6907-2008
|View full text |Cite
|
Sign up to set email alerts
|

Increase of the aerosol hygroscopicity by cloud processing in a mesoscale convective system: a case study from the AMMA campaign

Abstract: Abstract. Aerosol properties were measured during an airborne campaign experiment that took place in July 2006 in West Africa within the framework of the African Monsoon Multidisciplinary Analyses (AMMA). The goal of the present study was to determine the main microphysical processes that affect the aerosols during the passage of a mesoscale convective system (MCS) over the region of Niamey in Niger. A significant change in the aerosol profiles measured before and after the passage of the MCS was found in a la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 46 publications
2
74
0
Order By: Relevance
“…The heterogeneous processes responsible for sulphate mixing with dust may be season-dependent with predominance of coagulation process in summer and SO 2 uptake in spring (Suzuki et al 2010). Recent observations of strong internal mixing of dust with nitrate or sulphate in mesoscale convective clouds during the AMMA campaign (Crumeyrolle et al 2008;Matsuki et al 2010a) suggest in-cloud processing involving aqueous phase oxidation of NOx/SO 2 , as previously assumed by Levin and Ganor (1996) and Liu et al (2005 (Krueger et al 2004) and then observed in recent field studies (Laskin et al 2005;Matsuki et al 2005Matsuki et al , 2010bShi et al 2008;Huang et al 2010;Suzuki et al 2010). …”
Section: Internal Mixing Dust/inorganic Speciessupporting
confidence: 63%
“…The heterogeneous processes responsible for sulphate mixing with dust may be season-dependent with predominance of coagulation process in summer and SO 2 uptake in spring (Suzuki et al 2010). Recent observations of strong internal mixing of dust with nitrate or sulphate in mesoscale convective clouds during the AMMA campaign (Crumeyrolle et al 2008;Matsuki et al 2010a) suggest in-cloud processing involving aqueous phase oxidation of NOx/SO 2 , as previously assumed by Levin and Ganor (1996) and Liu et al (2005 (Krueger et al 2004) and then observed in recent field studies (Laskin et al 2005;Matsuki et al 2005Matsuki et al , 2010bShi et al 2008;Huang et al 2010;Suzuki et al 2010). …”
Section: Internal Mixing Dust/inorganic Speciessupporting
confidence: 63%
“…It was extended with the sectional aerosol model ORISAM (Cousin et al, 2004) as well as with the three-moments aerosol scheme ORILAM for the simulation of aerosol dynamics and secondary inorganic and organic aerosols (Tulet et al, 2005), which laid the foundation for studies of chemistrymeteorology feedbacks. MesoNH-C was subsequently employed for a wide range of applications to study the effect of biogenic emissions on regional O 3 levels (Solmon et al, 2004), the impact of convection on aerosol hygroscopicity (Crumeyrolle et al, 2008), for regional scale CO 2 source inversion (Lauvaux et al, 2009), sulfur transport and chemical conversion in a volcanic plume (Tulet and Villeneuve, 2011), or to investigate Saharan dust transport (Bou Karam et al, 2010) to name but a few.…”
Section: Applications Without Feedbacksmentioning
confidence: 99%
“…Tang (tangj@cams.cma.gov.cn) metry factor, etc. ), which could enhance the cooling effect of aerosols in the atmosphere by directly scattering more light radiation (Carrico et al, 1998(Carrico et al, , 2000Kotchenruther et al, 1998;Randles et al, 2004), or change cloud microphysical properties (Crumeyrolle et al, 2008) by serving as cloud condensation nuclei (CCN) (Houghton et al, 2001). To precisely evaluate the direct radiative forcing, light scattering coefficient (σ sp ) of aerosol particles and its dependency on relative humidity (RH), defined as f (RH)=σ sp (scanning RH)/σ sp (dry), have been investigated for decades through Integrating Nephelometers equipped with humidity control devices in clean background regions, marine boundary layers, rural and urban areas (Kotchenruther et al, 1999;Malm et al, 2001Carrico et al, 2003;Magi et al, 2003;Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%